Exploring Team Growth and Fixed Mindsets in Work Teams at a Large Korean Corporation - Soo Jeoung Han; Bora Jin; Jihye Oh (Adult Education Research Conference, 2019)
We conducted a qualitative study to understand how team mindsets can be manifested in work teams. We interviewed 21 participants from seven departments in one of the big corporations in Korea.
Keywords: growth mindset; fixed mindset; team mindset; implicit person theory